Code-switching and code-mixing used by an Indonesian Vtuber on YouTube - Shafa Arlene Salsabila (Passage: Journal of English Language and Literature, 2023)
This research aims to identify the types of code-switching and code-mixing used by an Indonesian VTuber and the functions behind them. The data are taken from a live-streamed video of an Indonesian VTuber, Kobo Kanaeru, on YouTube. Descriptive qualitative method is employed in conducting this research. Several theories are used in the analyzing process of this research, such as Hoffmann (2017), Wardhaugh (2005), and Crystal (2008) to identify and analyze the code-switching and code-mixing types. Hoffman (2017) is also used to analyze the functions of the code-switching and code-mixing. The findings of this research discover that intra-sentential switching and intra-sentential mixing are the dominant types of code-switching and code-mixing. This shows that Kobo preferred to do code-switching and code-mixing for shorter English clauses and words only, and it indicates that Kobo is not very fluent in speaking English. It is also found that Kobo used code-switching and code-mixing mostly to talk about a particular topic. It is because in her live-streamed video, she only talks about the game she is playing in her live-streaming or other topics that comes from her viewers in the comment section.